A comprehensive survey of the analytical, numerical and experimental methodologies for dynamics of multibody mechanical systems with clearance or imperfect joints. (April 2018) - Tian, Qiang; Flores, Paulo; Lankarani, Hamid M.
Highlights: A complete and detail review of the analytical, numerical and experimental methodologies on the topic of clearance joints is presented. Several different types of clearance joints existing in planar and spatial mechanisms are characterized. Models for dry and lubricated joints are individually addressed and compared. Experimental investigations on mechanical systems with clearance joint are discussed. Potential areas for further developments and future challenges in clearance joint studies are highlighted. Abstract: A comprehensive survey of the literature of the most relevant analytical, numerical, and experimental approaches for the kinematic and dynamic analyses of multibody mechanical systems with clearance joints is presented in this review. Both dry and lubricated clearance joints are addressed here, and an effort is made to include a large number of research works in this particular field, which have been published since the 1960′s. First, the most frequently utilized methods for modeling planar and spatial multibody mechanical systems with clearance joints are analyzed, and compared. Other important phenomena commonly associated with clearance joint models, such as wear, non-smooth behavior, optimization and control, chaos, and uncertainty and links' flexibility, are then discussed. The main assumptions procedures and conclusions for the different methodologies are also examined and compared. Finally, future developments and new applications of clearance joint modeling and analysis are highlighted.